The Meaning of Justice from a Mass Communication Perspective in the Film Keadilan (2025) - Bintang Alfu Nugraha; Nunik Hariyani; Fikri hasan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the meaning of justice constructed in the film Keadilan (The Verdict, 2025) directed by Lee Chang-hee and Yusron Fuadi through a mass communication perspective using Stuart Hall's encoding/decoding theory. This Indonesian–South Korean collaboration consistently raises critiques of the legal system, class-based impunity, and institutional failures of the judiciary. The study employs a qualitative-interpretive textual analysis method. The analysis reveals that the film encodes three layered dimensions of justice: (1) procedural justice as an object of critique, where formal legal systems are portrayed as mechanisms vulnerable to manipulation by power and capital; (2) distributive justice as an ideological substructure affirming that access to legal protection follows lines of socioeconomic inequality; and (3) restorative justice as deliberate ambiguity, inviting audiences to reflect on the boundary between justice and revenge. Through narrative, character construction, mise-en-scène, cinematography, and dialogue, the film positions itself in an encoding stance of strategic subversive complicity using popular genre forms as vehicles for substantial social critique. These findings affirm the relevance of Hall's theory in dissecting film texts as arenas of ideological meaning contestation, particularly within the context of legal and justice representation in Indonesia.